1999
DOI: 10.1097/00132586-199906000-00054
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Pain and Well Being: a World Health Organization Study in Primary Care

Abstract: Context.-There is little information on the extent of persistent pain across cultures. Even though pain is a common reason for seeking health care, information on the frequency and impacts of persistent pain among primary care patients is inadequate.Objective.-To assess the prevalence and impact of persistent pain among primary care patients.Design and Setting.-Survey data were collected from representative samples of primary care patients as part of the World Health Organization Collaborative Study of Psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
613
2
63

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 538 publications
(709 citation statements)
references
References 0 publications
31
613
2
63
Order By: Relevance
“…Anxiety and anger were also common in this population. Table 7 Factors associated with severe chronic pain -Logistic regression analyses were performed to identify variables that distinguished patients with severe pain (C 7/10) from those who had pain of lesser intensity (\ 7/10) Numerous epidemiological and clinical studies [25][26][27][28][29][30] have documented the high prevalence of psychological comorbidities in patients with chronic pain, especially in those who experience significant limitations in their activities of daily living due to pain. For example, an international WHO survey of nearly 26,000 patients attending primary care facilities showed that chronic pain sufferers exhibited a four-fold increase in the odds of having an anxiety or depressive disorder relative to patients without persistent pain.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and anger were also common in this population. Table 7 Factors associated with severe chronic pain -Logistic regression analyses were performed to identify variables that distinguished patients with severe pain (C 7/10) from those who had pain of lesser intensity (\ 7/10) Numerous epidemiological and clinical studies [25][26][27][28][29][30] have documented the high prevalence of psychological comorbidities in patients with chronic pain, especially in those who experience significant limitations in their activities of daily living due to pain. For example, an international WHO survey of nearly 26,000 patients attending primary care facilities showed that chronic pain sufferers exhibited a four-fold increase in the odds of having an anxiety or depressive disorder relative to patients without persistent pain.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Thus, buprenorphine recipients report far higher rates of chronic pain than the 10 % prevalence estimated in the general US population by the World Health Organization. 15,16 Heterogeneous clinical conditions account for the sites of pain-low back, legs, total body-that comprise the majority of pain complaints among opioid-dependent patients. 6,17 Pain in this population has been attributed to past traumatic injuries, chronic medical conditions, human immunodeficiency virus and hepatitis C virus infection, 18,19 opioid-induced hyperalgesia, 20 and non-specific factors unrelated to opioid withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is the most frequent reason for medical visits and the direct economic impact of chronic back pain alone has been estimated to be as high as $86 billion annually, with indirect costs exceeding hundreds of billion dollars. 2 Providing treatment for CNCP is challenging and many patients continue to experience persistent pain and disability.…”
Section: Introductionmentioning
confidence: 99%